O Conselho de Escola como espaço de participação da comunidade - Ibraimo, Mahomed Nazir (2015)
In Moçambique, the inclusion of external communities within schools became evident in the post-independence period when the first experiments were undertaken to include parents and guardians through parents’ committees and strengthen the linkage between the school and the community. The law 6/92 of 6th of May, re-enforces this inclusion and recognizes the participation of other entities, including that of communities, in the management of 2 the educational process and gives incentive to a greater connection between the community and the school. School councils are born from the need for openness between the school and the local community. The Ministerial Diploma 54/2005, 28th of May, accordingly seeks to create a greater degree of flexibility, via administrative decentralization, in the decision-making process in schools through participative management. This article, as part of the author’s doctoral studies, aims to understand how the actors who constitute a secondary school’s council perceive their participation in its decision-making process. A qualitative, exploratory approach was adopted in order to interpret the reality within a complex vision. Data was collected via interviews, analysis of minutes of council meetings and observation of the School Council in session. Results indicate that there is a good relationship between the members of the council and the school and, that the school encourages participation of external parties in the meetings. Results also show that the council meetings deal with pedagogic issues, principally with questions related to the behaviour of pupils and teachers and that the external members are concerned with these issues and seek to contribute ideas, opinions and solutions. These contributions made by parents and guardians are accepted and valued when they are in accordance with the established order of school governance. However, results also indicate that as far as decision-making is concerned, it is the school director who makes the final decision and controls the discussions thereby leaving the external members of the school council with little impact on the decision-making process. Data collected indicates that school councils operate under the influence of organizational bureaucracy, micro-politics, anarchy and hypocrisy.